2015
DOI: 10.1177/0300985815588609
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Bolivian Hemorrhagic Fever in Guinea Pigs

Abstract: Machupo virus, the cause of Bolivian hemorrhagic fever, is a highly lethal viral hemorrhagic fever with no Food and Drug Administration-approved vaccines or therapeutics. This study evaluated the guinea pig as a model using the Machupo virusChicava strain administered via aerosol challenge. Guinea pigs (Cavia porcellus) were serially sampled to evaluate the temporal progression of infection, gross and histologic lesions, and sequential changes in serum chemistry and hematology. The incubation period was 5 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
2
23
0
1
Order By: Relevance
“…Studies are under way to determine the cause of the attenuation. Recent studies have identified another strain of MACV, strain Chicava, to be 100% lethal in Hartley guinea pigs (55). Ongoing studies are examining the protective effect of DNA vaccinederived antibodies against strain Chicava.…”
Section: Discussionmentioning
confidence: 99%
“…Studies are under way to determine the cause of the attenuation. Recent studies have identified another strain of MACV, strain Chicava, to be 100% lethal in Hartley guinea pigs (55). Ongoing studies are examining the protective effect of DNA vaccinederived antibodies against strain Chicava.…”
Section: Discussionmentioning
confidence: 99%
“…Our animal experiments involved the use of IFN-␣␤/␥ R Ϫ/Ϫ mice. A study in animals with an intact interferon pathway, such as guinea pigs or NHPs, as recently described (28,29), is required for the development of a safe and efficacious vaccine against MACV infection. Our study also highlights the feasibility of attenuating other highly pathogenic New World arenaviruses, such as Guanarito virus, following the same approach by introducing the GPC gene from the Cd#1 vaccine strain of JUNV.…”
Section: Figmentioning
confidence: 99%
“…Neurological symptoms are common during NW arenavirus infection. This correlates with robust viral replication in neurological tissues as evidenced by high viral titers in the brains of infected animals [52,102]. MACV antigen can also be preferentially detected within neurons [52].…”
Section: Impacts Of the Adaptive Cellular Immune Response On Post-infmentioning
confidence: 71%
“…This correlates with robust viral replication in neurological tissues as evidenced by high viral titers in the brains of infected animals [52,102]. MACV antigen can also be preferentially detected within neurons [52]. Interestingly, treatment of AHF and BHF with convalescent serum increases the likelihood of developing a long-term neurologic syndrome [43,103].…”
Section: Impacts Of the Adaptive Cellular Immune Response On Post-infmentioning
confidence: 99%
See 1 more Smart Citation